PENGARUH PEMBELAJARAN KOOPERATIF MODEL NUMBERED HEAD TOGETHER (NHT) TERHADAP PENINGKATAN PENGETAHUAN SISWA PADA MATA PELAJARAN IPA - Rahman, Imas Kania; Hapizzudin, Moh; Arif, Suyud (ATTA`DIB, 2016)
The result of the research shows that application of cooperative learning Numbered Head Together (NHT) model is quietly good, because every steps of application increase well and regularly. The first cycle 75,83% increases to the second one 83,83% and increase regularly to the third one 89,66%. The score of students’ learning outcome from first cycle 63,33% increases to the second one 83,33% and increases regularly to the third one 100%. It can be concluded that cooperative learning in such model becomes good solution to the increasing the students’ knowledge.